Human in vivo assessment of ketamine binding of the serotonin transporter—follow up at a higher dose - Schlosser, G.; Murgaš, M.; Godbersen, G. M.; Reichel, S.; Silberbauer, L.; Nics, L.; Winkler, D.; Stimpfl, T.; Hacker, M.; Kasper, S.; Rujescu, D.; Lanzenberger, R.; et al. (Frontiers in Neuroscience, 2025)
Ketamine is a rapid-acting antidepressant approved in the indication of treatment-resistant depression. As its clinical use expands, identifying underlying molecular mechanisms is essential. The serotonin transporter (SERT) is well known as a primary mechanism of several classes of monoaminergic antidepressants. Binding of ketamine to SERT has been observed in vitro and in animal studies with macaque monkeys using positron emission tomography (PET). We previously reported that a 0.5 mg/kg body weight dose of ketamine did not significantly bind to SERT in healthy human subjects assessed with PET but observed a positive trend between binding and ketamine plasma levels. Based on this finding, we hypothesized that a higher dose (0.8 mg/kg) would result in measurable SERT occupancy. Here, 10 healthy male participants were measured twice with [11C]DASB PET to test SERT occupancy following administration of 0.8 mg/kg body weight ketamine in four selected SERT rich regions amygdala, putamen, caudate and thalamus. Further, we implemented a bolus-plus-infusion radioligand infusion protocol and optimized the timing of the ketamine infusion. Contrary to our hypothesis, ketamine SERT occupancy did not significantly differ from zero, and the area under the curve of ketamine and norketamine plasma levels was not correlated with occupancy. These results suggest that even at doses up to 0.8 mg/kg, ketamine does not appreciably bind to SERT in humans, aligning with clinical observations that ketamine is routinely combined with serotonergic agents.Clinical trial registrationhttp://clinicaltrials.gov, identifier, NCT02582398. EUDAMED number, CIV-AT-13-01-009583.